For an overcoat, a suitcase and an apple. Crimes against Jews hiding in the villages of Falkowa, Wieniec and Janowice in ... - Dagmara Swałtek (Zagłada Żydów)
The article contains a discussion and an attempt at analysis of the post-war investigation and trial materials regarding three different cases of murder or denunciation of hiding Jews by the local Polish population. The crimes discussed in the article took place in three villages, which during the occupation were located in the Cracow district: Falkowa, Wieniec and Janowice. After the war the perpetrators were indicted on the basis of the Decree of 31 August 1944, i.e. the so-called “August Decree”. According to the testimonies of the witnesses and the defendants, the main motive behind the murder of Jews or their denunciation to the occupier was the desire for quick material gain, and, secondly, the fear of the consequences if the information that the Jews were hiding in the village reached the authorities. Another important element of the incidents was the active or passive participation of numerous village dwellers in the crimes